Genre Analysis of Body Horror in Contemporary Hollywood Films (The Substance, Bodies Bodies Bodies, and It’s What’s Inside) - Aulia Rahmawati; Farrel Rakha Adi Pramana (International Journal of Social, Economic, and Business, 2025)
This article examines the dynamics of the body horror genre in three recent Hollywood films: The Substance (2024), Bodies Bodies Bodies (2022), and It’s What’s Inside (2024). Utilizing Nick Lacey’s "repertoire of elements" model, the study dissects how body horror functions as a site of cultural and ideological discourse, encompassing themes of identity, beauty, technology, and social criticism. Through detailed narrative, character, iconographic, setting, and stylistic analysis, the research demonstrates how body horror, far from being mere spectacle, operates as a potent metaphor for anxieties surrounding the human condition in contemporary society. The findings reveal that these films push the boundaries of horror to engage in a critique of body politics, gender norms, performative culture, and capitalist commodification.